Rent Seeking In The Illegal Gold Mining Business Network In West Sumatra Province (A Case Study Of Sijunjung And South Solok Regencies) - Anggraini, Dewi; Fajri, Mhd; Islami, Syaifuddin (JOELS: Journal of Election and Leadership, 2023)
Rent-seeking practices in illegal gold mining activities take the form of mutually beneficial collaborations between authorities and entrepreneurs/owners of capital. Various parties profit from these gold mining activities, including both mining groups and certain individuals within the ranks of officers, officials, and bureaucrats. This study aims to elucidate the causal factors and actors involved in illegal gold mining activities in the Sijunjung and South Solok Regencies. The theory employed for this study is the rent-seeking theory. The research methodology employs a qualitative case study approach with informants selected through purposive sampling. Data collection is conducted through interviews, observations, and documentation. The research findings indicate several causal factors contributing to rent-seeking. Firstly, there exists an interplay of interests between local governments and mining entrepreneurs. Secondly, there are instances of officers or bureaucrats who provide support for illegal mining activities. Typically, these mining operators pay a certain amount to these individuals to secure their mining equipment's ingress and egress. Additionally, a number of officers, bureaucrats, and even legislative personnel possess equipment for illegal gold mining. Thirdly, the lack of oversight by local governments over illegal gold mining activities is a contributing factor. In the practice of rent-seeking within the mining sector, corporations/entrepreneurs/capital owners, government officials, law enforcement authorities, and landowners are all involved